Time-periodic oscillation reaction in an organic-solvent dominated electrolyte. Issue 40 (6th October 2017) - Chang, Yu; Zhang, Nannan; Yang, Yuxin; Du, Jun; Fan, Xing; Tao, Changyuan
Abstract : Periodic potential oscillation in organic electrolytes has been observed and analyzed to inspire new strategies on improving energy conversion cells. Abstract : Time-periodic phenomena widely exist in natural life sustaining systems but are rarely reported in highly efficient artificial electrochemical energy-harvesting systems. Herein, we observed for the first time the periodic oscillation reaction in organic-solvent dominated electrolytes that could be also derived from some electrochemical energy harvesting cells. Owing to different reaction activity and acidity in the organic solvent, the oscillation reaction could occur under milder pH conditions and exhibit better durability. Its influence on electric output and related differences from an aqueous B–Z reaction are discussed from a mechanism point of view. Our findings may contribute to smart self-oscillation materials and new strategies for highly efficient long-term energy harvesting.